Speaking Personally with Dr. Michael Beaudoin. Issue 3 (2nd July 2020) - Shattuck, Kay
ABSTRACT: Perhaps now, as I write in the pandemic confusion of education, there is renewed, or shall I say, long overdue interest in exploring leadership and policy topics in distance education. Thus, it is our pleasure to interview Dr. Michael Beaudoin. Dr. Beaudoin has authored 130 publications and presentations, including three books – one winning the prestigious Wedemeyer Award, as well as continuing to contribute articles and chapters, such as the chapter on institutional leadership (Beaudon, 2019 ) in the 4 th edition of the Handbook on Distance Education .